The Generalized Autoregressive Conditional Heteroscedasticity Model Application on Inflation and Consumers Price Index in Aceh - Sri Hasnanda; Ratna Ratna (Journal of Malikussaleh Public Economics, 2020)
This study aimed to analyze the application of Generalized Autoregression Conditional Heteroscedasticity (GARCH) on inflation and consumer price index in Aceh Province. The data used in this study is secondary data sourced from the Central Statistics Agency (BPS) of Aceh Province with a period of 2013-2018 on a monthly basis. The data analysis method used is the ARIMA for mean model GARCH for variance models. The results of this study indicate that the Mean Model for Inflation uses the AR (1) and MA (1) components, while the Mean Model for consumer price index is AR (1). Meanwhile, the Variance Model with GARCH estimates for inflation and consumer price index data has insignificant RESID^2 (1) and GARCH (1).Keywords: Inflation, CPI and Generalized Autoregression Conditional Heteroscedasticity (GARCH)